The influence of chemical composition of amide block on the thermal properties and structure of terpoly(ester-b-ether-b-amide) elastomers - Ukielski, R.; Piątek, R. (Polimery, 2022)
Multiblock terpolymers-(PBT-b-PTMO-b-PA12,10)(n)- constituting the polymer systems, in which one of the three blocks (PBT) does not dissolve in PA12,10 block (hard phase) and, depending on its molecular weight is slightly soluble in PTMO block (soft phase), have been obtained. The DSC method was applied to investigate the thermal properties of these polymers and it was found that PBT block acts as an element that produces stiffness of -(PBT-b-PTMC-b-PA12,10)(n)- structure. Thus, this block causes deterioration of the elastic properties and leads to the formation of terpolymers showing the features of reinforced plastics. The terpolymers were compared with the previously described [5] -(PBT-b-PTMO-b-PA12)(n)-. They are elastomers when the rigid PBT block’s polymerization degree is in the range 4-7. Such a block the rigid PBT block - dissolves in the hard phase of PA12 blocks and partly dissolves in the soft phase. So, it was found that even a small change in the chemical structure of the amide block influences significantly on the structure, phase separation and the properties of terpolymers. An analysis of the thermal properties of -(PBT-b- PTMO-b-PA12,10)(n)- confirms an argument that the block terpolymers show good elastic properties only in case when one of the blocks partly dissolves in the phases formed from the remaining blocks.